ANALISA KEBERSIHAN PANEL SURYA TERHADAP KELUARAN PLTS ON-GRID 200 KWP BANDARA UDARA SULTAN MUHAMMAD SALAHUDIN BIMA - Sandrawati, Syafiatun; Satya kumara, I Nyoman; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUM, 2023)
Sultan Muhammad Salahuddin Bima Airport is one of the few airports in Indonesia that has PLTS as a supplier of electrical energy. The existence of PLTS at each airport is a concern for further analysis, so that the potential for electrical energy production from PLTS can be optimal. So the solar module which is the main component of PLTS is very important to pay attention to cleanliness from dirt or dust that can reduce the efficiency and electricity production of PLTS. The measurement of PLTS energy production at Sultan Muhammad Salahuddin Bima Airport before cleaning was 567.56 kWh and after cleaning it was 576.86 kWh. In this measurement, cleaning was carried out on a series of 1 Inveter with a total of 100 solar panels. There is a change in energy production from the measurement results. This condition is due to solar panels that have not been cleaned for 1 year. So that the percentage increase in PLTS energy production at Sultan Muhammad Salahuddin Bima Airport is 1.63%.